A new species of the genus Allopsontus Silvestri (Archaeognatha: Machilidae) from the Eastern Kazakhstan - Kaplin, Vladimir M. (Zootaxa, 2018)
A new bristletail species, Allopsontus ilyai sp. nov., is described from Eastern Kazakhstan. It is most similar to A. smelyanskii Kaplin described from Orenburg Region (Russia). The main differences between these species consist in the color of the eyes, structure of the paired ocelli, legs, urosternites, urocoxites VIII and IX. A key to the subgenera and species of the genus Allopsontus from Kazakhstan is given.